Interspecies Kinship of Liuran: Rethinking Marshall Sahlinss Mutuality of Being - Hardiah, Sofiatul (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2023)
The anthropological discussions regarding the concept of mutuality of being by Marshal Sahlins have focused on the idea that kinship only occurs between humans through certain rituals or traditions. This idea is limited in considering non-human species that also potentially form interspecies kinship. Through a multispecies ethnographic approach, this article discusses interspecies kinship in the context of joint agricultural care without exchanging exact amount of payment (liuran) by female farmers in Kampung Laut District, Cilacap Regency, Indonesia. In this study, the data were collected through participant observation techniques and in-depth interviews with four female farmers as key informants who have been involved in liuran for years. The findings showed that the interspecies kinship between female farmers and rice and garden crops is like mother and child because there has been an emotional-ecological bond in the process of caring for sedimentation farming over decades, primarily through taboo practices. The process of caring for rice and garden plants together also forms a socio-economic support system among female farmers, which helps strengthen their interspecies kinship. Considering non-human species as part of the family members places them in an equal relationship with humans in contributing to the sustainability of living ecosystems.